LA VARIATION LIBRE PHONOLOGIQUE ET MORPHOLOGIQUE DU DIALECTE NIÇOIS : ESSAI D’ILLUSTRATION - GIUDICE, Philippe Del (Studia Universitatis Babeș-Bolyai Philologia, 2022)
Phonological and Morphological Free Variation in the Dialect of Nice – an Illustration. A project has been launched to make a dialectal dictionary of Nice and its surroundings. As an important amount of data is being gathered from various texts and in the field, the proportion of free variation in the Occitan dialect spoken in the city of Nice appears to be significantly greater than what studies (especially grammars and dictionaries) report. Using a substantial set of examples, this descriptive article shares with the scientific community some important features of phonological and morphological polymorphism in urban Niçois. In the phonological part, it also shows the links that tie together polymorphism and diatopic variation in a relatively homogeneous dialectal area. Article history: Received 14 July 2021; Revised 1 January 2022; Accepted 10 January 2022; Available online 31 March 2022; Available print 31 March 2022. REZUMAT. Variaţia liberă fonologică şi morfologică în dialectul nisard – o prezentare. Un proiect de realizare a unui dicţionar dialectal din regiunea Nisei a fost lansat. În timp ce informaţiile de ordin dialectal sunt preluate masiv din sursele textuale şi din teren, fenomenele de variaţie liberă din dialectul occitan de la Nisa se dovedesc a fi mult mai numeroase decât cele prezente în studiile existente (mai ales în gramatici şi în dicţionare). Bazându-se pe un număr însemnat de exemple, acest articol descriptiv împărtăşeşte comunităţii ştiinţifice câteva aspecte importante ale polimorfismului fonologic şi morfologic al nisardei urbane. Perspectiva fonologică este, de altfel, o bună ocazie de a arăta legăturile care unesc polimorfismul şi variaţia diatopică într-o arie dialectală omogenă. Cuvinte-cheie: variaţie liberă, fonologie, morfologie, dialectul nisard, occitană